Preparation method of biomimetic membrane coated ferrous sulfide nano material based on neutral particles as well as product and application of biomimetic membrane coated ferrous sulfide nano material

By preparing ferrous sulfide nanomaterials wrapped with bionic membrane based on neutral particles, the problem of lack of specificity of tumor treatment and limited CDT efficacy in the prior art is solved, tumor-specific targeting and efficient ROS generation are achieved, which significantly improves the anti-tumor effect and reduces side effects.

CN119656110APending Publication Date: 2025-03-21HANGZHOU FIRST PEOPLES HOSPITAL +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411575898.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing cancer treatments lack tumor specificity, resulting in damage and side effects to normal tissues, and the efficacy of chemokinetic therapy (CDT) is limited by the concentration of tumor microenvironment substrates, making it difficult to achieve efficient ROS generation and tumor-specific killing.

Method used

By preparing ferrous sulfide nanomaterials wrapped with bionic membranes based on neutrophils, the nanomaterials are wrapped on the neutrophil membrane using ultrasonic treatment technology to achieve tumor-specific tendency and efficient enrichment, and then release H2S and Fe2+ in the acidic tumor microenvironment, amplify the Fenton reaction, and generate highly active ROS.

Benefits of technology

Tumor-specific targeting and efficient ROS generation have been achieved, which significantly improves the anti-tumor effect, reduces the toxic side effects on normal tissues, and has good biosafety and clinical application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119656110A_ABST
    Figure CN119656110A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a bionic membrane coated ferrous sulfide nano material based on neutral grains, which comprises the following steps: dissolving bovine serum albumin in deionized water, adding a ferrous chloride tetrahydrate solution and a sodium sulfide solution to obtain a mixed solution, and reacting to obtain an albumin embedded amorphous ferrous sulfide nano material; mixing a neutrophile granulocyte membrane solution, a lipidosome solution and the albumin chimeric amorphous ferrous sulfide nano-material, and performing ultrasonic treatment to obtain the biomimetic membrane coated ferrous sulfide nano-material. The invention also discloses the biomimetic membrane coated ferrous sulfide nano-material obtained by the preparation method and application of the biomimetic membrane coated ferrous sulfide nano-material in preparation of tumor treatment drugs. The biomimetic membrane coated ferrous sulfide nano-material prepared by the invention can realize tumor specificity trend, effectively improves enrichment of the ferrous sulfide nano-material at a tumor site so as to realize efficient tumor specificity killing, and has good biological safety to normal tissues.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of bionic carrier and ferrous sulfide nano material preparation, and in particular to a preparation method of ferrous sulfide nano material wrapped by a bionic membrane, and a product and application thereof. Background Art

[0002] Cancer is one of the major diseases that seriously threaten human health worldwide. Traditional cancer treatments include surgical resection, chemotherapy, and radiotherapy. However, surgical resection often has problems such as incomplete resection of lesions, which often causes tumor recurrence and metastasis; in addition, although radiotherapy and chemotherapy can alleviate the progression of cancer to a certain extent, due to the lack of specificity for tumors, it often causes indiscriminate damage to normal tissues, thereby causing serious side effects. Therefore, in order to improve the specificity of tumor treatment and reduce the toxic side effects of treatment, it is urgent to develop a treatment model with more tumor-selective killing effect.

[0003] In recent years, chemodynamic therapy (CDT) has attracted widespread attention as an emerging non-invasive cancer treatment method because it relies on the characteristics of the tumor microenvironment (TME) (such as acidic and rich in hydrogen peroxide (H2O2)) to achieve selective killing of tumors. CDT can catalyze H2O2 in the tumor site to generate highly active hydroxyl radicals (·OH), thereby effectively killing tumor cells by triggering the Fenton or Fenton-like reaction. However, the efficacy of CDT is often limited by the concentration of substrates in the TME: on the one hand, the high expression of antioxidant enzymes (such as catalase (CAT)) in tumor cells will quickly decompose H2O2 in the tumor site, thereby reducing the efficiency of reactive oxygen species (ROS) generation; on the other hand, the limited acidity of the tumor site also limits the catalytic effect of the Fenton reaction. Therefore, if it is possible to achieve the selective killing of H2O2 and H + The effective accumulation of, that is, increasing the substrate concentration of the Fenton reaction, will hopefully increase the Fenton reaction efficiency and ROS yield, and enhance the CDT treatment effect.

[0004] In addition, in order to improve the delivery effect of therapeutic drugs in the complex and dynamic in vivo environment, reduce the nonspecific distribution and potential toxic side effects of drugs in normal tissues, increase the blood circulation time of drugs and the targeting effect on tumor lesions, it becomes the key. In view of this, the commonly used strategy in current research is to introduce polyethylene glycol (PEG) or some targeting ligands (such as targeting peptides, small molecules and antibodies) into the system. However, these introduced "exogenous" materials often have certain immunogenicity or require complex and cumbersome subsequent modification processes, and more and more studies have reported that excessive or repeated use of PEG may also accelerate its in vivo immune clearance and reduce its in vivo circulation time. Therefore, it is particularly important to develop a delivery carrier that can effectively overcome the in vivo barrier and has a tumor targeting effect. The biomimetic strategy based on cell membrane coating provides a new solution for improving the in vivo delivery efficiency and targeting of drugs. Among them, neutrophils, as the most abundant type of white blood cells in the body (accounting for about 50-75%), are the first line of defense for the host to resist invading pathogens. When pathogens invade, they can be quickly activated and migrate to the damaged area. And it is involved in the progression of tumors. When cancer occurs, tumor tissues will secrete some chemokines to recruit neutrophils. Neutrophils can pass through the vascular endothelium and migrate to the inflammation and tumor areas under the recruitment of chemokines. Therefore, neutrophil-based carriers are expected to overcome the biological barriers in the body and achieve tumor targeting. In addition, by wrapping nanomaterials with neutrophil membranes, the biocompatibility of nanomaterials can be improved and the stability of nanomaterials can be enhanced.

[0005] Therefore, there is an urgent need to develop a biomimetic membrane-wrapped efficient Fenton nanomaterial that can specifically target tumors and reduce their nonspecific distribution in normal tissues, so as to achieve efficient ROS generation and tumor-specific killing at the tumor site. Summary of the invention

[0006] The present invention aims to provide a method for preparing a biomimetic membrane-wrapped ferrous sulfide nanomaterial based on neutral particles. The prepared biomimetic membrane-wrapped ferrous sulfide nanomaterial can achieve tumor-specific tendency, effectively improve the enrichment of ferrous sulfide nanomaterial in the tumor site, so as to achieve efficient tumor-specific killing, and have good biosafety to normal tissues.

[0007] The technical solution provided by the present invention is:

[0008] The present invention provides a method for preparing a ferrous sulfide nanomaterial wrapped by a biomimetic membrane based on neutral particles, the method comprising the following steps:

[0009] S1. dissolving bovine serum albumin in deionized water, adding ferrous chloride tetrahydrate solution and sodium sulfide solution to obtain a mixed solution, and reacting to obtain an albumin-embedded amorphous ferrous sulfide nanomaterial (referred to as ferrous sulfide nanomaterial);

[0010] S2. Mixing the neutrophil membrane solution, the liposome solution and the albumin-embedded amorphous ferrous sulfide nanomaterial, and subjecting the mixture to ultrasonic treatment to obtain the bionic membrane-wrapped ferrous sulfide nanomaterial.

[0011] In the preparation method provided by the present invention, the ferrous sulfide nanomaterial is synthesized by a self-assembly method: when ferrous chloride is added to a bovine serum albumin solution, the divalent iron ions combine with the functional groups in the bovine serum albumin to form a stable bovine serum albumin-Fe 2+ (BSA-Fe 2+ ) complex; after adding sodium sulfide solution, S 2- Ions in BSA-Fe 2+ The ferrous sulfide diffuses in the complex, inducing the nucleation of ferrous sulfide, and obtaining an albumin-embedded amorphous ferrous sulfide nanomaterial. The amorphous structure lays a good chemical catalytic foundation for the subsequent application of ferrous sulfide nanomaterials. The biomimetic membrane carrier of the present invention is prepared by a probe ultrasound method: the cell membrane fragments are hybridized with liposomes to obtain a biomimetic membrane based on neutrophils. The inflammation-targeting related proteins on the biomimetic membrane are retained, laying the foundation for the subsequent tumor inflammation tropism and targeted delivery of ferrous sulfide nanomaterials to achieve tumor-specific treatment.

[0012] The present invention optimizes the preparation method of nanomaterials and carriers and the construction of the delivery system, and the obtained bionic delivery system can achieve tumor-specific tendency and effectively improve the enrichment of ferrous sulfide nanomaterials in the tumor site. After reaching the tumor area, the ferrous sulfide nanomaterials decompose into H2S gas and Fe in the acidic TME. 2+ H2S can promote the accumulation of intracellular H2O2 by inhibiting the CAT activity of tumor cells, and at the same time promote the accumulation of intracellular lactic acid, thereby expediting the Fenton reaction to achieve efficient CDT anti-tumor therapy. This strategy can achieve efficient tumor-specific killing and has good biosafety for normal tissues.

[0013] In step S1, the feed ratio of bovine serum albumin, deionized water, ferrous chloride tetrahydrate and sodium sulfide is 10-100 mg: 4-12 mL: 2-12 mg: 1-8 mg.

[0014] Preferably, the feeding ratio of bovine serum albumin, deionized water, ferrous chloride tetrahydrate and sodium sulfide is 20-60 mg: 6-10 mL: 4-8 mg: 2-6 mg.

[0015] In step S1, ferrous chloride tetrahydrate solution and sodium sulfide solution are added in sequence under stirring at 1200 rpm or more, the reaction temperature is 1-8°C, and the reaction time is 6-24h; preferably, the reaction temperature is set to 4°C, and the reaction time is 10-14h.

[0016] The present invention also includes removing excess reactants from the obtained ferrous sulfide nanomaterial by dialysis, the dialysis temperature is 1-8°C, and the dialysis time is 6-24h; preferably, the dialysis temperature is set to 4°C, and the dialysis time is 10-14h.

[0017] The ferrous sulfide nanomaterial is uniformly spherical and has a size of 50 to 150 nanometers. The nanometer size is conducive to being taken up by tumor cells and improving its enrichment in the tumor area. Since the synthesized ferrous sulfide nanomaterial is an amorphous structure, more catalytic active sites are exposed, which can further enhance its Fenton reaction activity, thereby catalyzing H2O2 to generate cytotoxic ·OH, killing tumor cells.

[0018] Preferably, the diameter of the synthesized ferrous sulfide material is 115±20 nanometers.

[0019] Preferably, in step S1: the prepared ferrous sulfide nanomaterial is ferrous sulfide nanoparticles embedded with bovine serum albumin. In order to prepare ferrous sulfide nanomaterials embedded with bovine serum albumin of uniform size and morphology, ferrous chloride solution and sodium sulfide solution need to be added one by one to the bovine serum albumin solution under high-speed stirring (greater than or equal to 1200rpm). Among them, ferrous chloride needs to be quickly added to the bovine serum albumin solution under the condition of passing argon or other protective gas, and stirred for 10 minutes, so that the divalent iron ions diffuse and fully combine with the functional groups in the bovine serum albumin to form a stable bovine serum albumin-Fe 2+ (BSA-Fe 2+ ) complex. Then, sodium sulfide solution was quickly added, S 2- Ions in BSA-Fe 2+ The complex diffuses quickly and evenly, inducing the nucleation of ferrous sulfide. After 12 hours of aging reaction, the unreacted reagents are removed by dialysis to obtain albumin-embedded amorphous ferrous sulfide nanomaterials.

[0020] In step S2, the neutrophil-based biomimetic membrane described in the present invention is a hybrid membrane of neutrophil membrane and liposome. The neutrophil membrane is extracted by Percoll gradient method, and the neutrophil membrane is obtained by repeated freezing and thawing and centrifugation.

[0021] In step S2, the liposomes described in the present invention are prepared by a thin film dispersion method, the lipid used is lecithin, the solvent is chloroform, the rotary evaporation temperature is 20-60°C, and the rotary evaporation time is 0.5-4h; preferably, the rotary evaporation temperature is set to 40°C and the time is set to 1-2h.

[0022] In step S2, the feed ratio of the neutrophil membrane, liposome and ferrous sulfide nanomaterial described in the present invention is 0.5-2 mg: 1-4 mg: 0.5-6 mg. This ratio ensures the structural stability of the ferrous sulfide nanomaterial wrapped by the biomimetic membrane, as well as the targeting and drug release effect in the tumor microenvironment.

[0023] Preferably, the neutrophil membrane, liposome and ferrous sulfide nanomaterial are 0.5-1 mg: 1-2 mg: 1-1.5 mg. By adjusting this ratio, the structural stability of the ferrous sulfide nanomaterial wrapped by the biomimetic membrane, as well as the targeting and drug release effect in the tumor microenvironment can be further improved.

[0024] In step S2, the ultrasonic treatment power of the bionic membrane-wrapped ferrous sulfide nanomaterial described in the present invention is 8-20%, and the ultrasonic treatment time is 2-10 minutes; preferably, the ultrasonic treatment power is set to 10-15%, and the ultrasonic treatment time is 3-6 minutes.

[0025] The present invention also provides a bionic membrane-wrapped ferrous sulfide nanomaterial prepared by the above preparation method.

[0026] The present invention also provides the use of the above-mentioned biomimetic membrane-wrapped ferrous sulfide nanomaterial in the preparation of anti-tumor drugs. The use of the above-mentioned biomimetic membrane-wrapped ferrous sulfide nanomaterial in the preparation of specific tumor-targeting and tumor-inhibiting drugs. Through the inflammatory tendency mediated by neutrophil membrane proteins, the ferrous sulfide nanomaterial can specifically target and enrich in the tumor microenvironment, and achieve acid-responsive H2S and Fe in the tumor site. 2+ Release; Among them, H2S can reduce the CAT activity of tumor cells, promote the accumulation of H2O2, and promote the accumulation of intracellular lactic acid, thereby effectively amplifying the Fenton reaction, generating a large amount of ·OH to induce tumor cell apoptosis, and has significant anti-tumor effect and tumor killing specificity. Therefore, the biomimetic membrane-wrapped ferrous sulfide nanomaterial provided by the present invention can be used in the preparation of tumor treatment drugs to effectively achieve tumor-specific targeting and chemokinetic treatment effects.

[0027] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0028] (1) The preparation conditions of the Fenton preparation, bionic membrane carrier and bionic membrane-encapsulated nanoformulation system of the present invention are mild and controllable, with high repeatability and low cost, and have good potential for industrial production and clinical transformation.

[0029] (2) The present invention uses a biomimetic membrane based on neutrophils as a drug delivery carrier, and the therapeutic drugs can be effectively recruited to the tumor site, thereby significantly improving the enrichment efficiency of the drugs at the tumor site and reducing their specific distribution in normal tissues.

[0030] (3) Ferrous sulfide nanomaterials can achieve acid-responsive H2S and Fe in the tumor microenvironment 2+ Release, by amplifying the Fenton reaction, enhances the generation of ROS and significantly improves the anti-tumor effect.

[0031] (4) The ferrous sulfide nanomaterial wrapped by the biomimetic membrane of the present invention has low toxic side effects in non-tumor tissues, good biosafety, and has broad clinical application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 TEM image of the ferrous sulfide nanomaterial prepared in Example 1;

[0033] Figure 2 This is the XPS graph of the ferrous sulfide nanomaterial prepared in Example 1;

[0034] Figure 3 This is the XRD pattern of the ferrous sulfide nanomaterial prepared in Example 1;

[0035] Figure 4 This is a diagram showing the co-localization results of the ferrous sulfide nanomaterial prepared in Example 1 and the biomimetic membrane based on neutral particles;

[0036] Figure 5 This is a qualitative test result diagram of the total protein content of the ferrous sulfide nanomaterial system wrapped by the neutral particle-based bionic membrane prepared in Example 1;

[0037] Figure 6 This is a graph evaluating the efficiency of the ferrous sulfide nanomaterial prepared in Example 1 in generating ROS in the absence of H2O2;

[0038] Figure 7 This is a graph evaluating the efficiency of the ferrous sulfide nanomaterial in Example 1 in generating ROS under the condition of H2O2;

[0039] Figure 8 This is the H2S release diagram of the ferrous sulfide nanomaterial in Example 1;

[0040] Fig. 9 The Fe of the ferrous sulfide nanomaterial in Example 1 2+ Release diagram;

[0041] Fig.10 This is a diagram for evaluating the cytotoxicity of the ferrous sulfide nanomaterial wrapped by the bionic membrane in Example 1 to tumor cells;

[0042] Fig.11 This is a diagram evaluating the tumor inhibition effect of the ferrous sulfide nanomaterial wrapped by the bionic membrane in Example 1. DETAILED DESCRIPTION

[0043] The present invention is described in detail below with reference to the embodiments.

[0044] Example 1

[0045] (1) Neutrophils were extracted from the bone marrow of 6-week-old male ICR mice using a modified Percoll gradient method. The leg bones and femurs of the mice were first separated, and then the bone marrow was washed with RPMI 1640 medium, filtered through a 200 μm filter, and centrifuged at 1700 rpm for 5 min. Subsequently, the red blood cells were lysed twice using red blood cell lysis buffer, and the cells were washed and resuspended with pre-cooled PBS. Next, 78%, 65%, and 55% percoll separation solutions were slowly added to the centrifuge tube in sequence, and finally the cell suspension was added, and centrifuged at 3120 rpm for 30 min. Neutrophils at the 65% and 78% Percoll interfaces were collected, washed three times with pre-cooled PBS, and resuspended. In order to activate neutrophils, 100 ng of lipopolysaccharide (LPS) was added to stimulate the cells and cultured for 4 h at 37°C and 5% CO2. After the culture, the cell suspension was collected and centrifuged at 1700 rpm for 5 min, and then washed three times with pre-cooled PBS. Then, the cells were resuspended in deionized water and the neutrophil membranes were broken by repeated freezing-thawing. Specifically, the cell suspension was repeatedly frozen and cycled between -80°C and 37°C three times. Subsequently, the cell suspension was centrifuged at 15,000 rpm for 15 min, the neutrophil membranes were collected at 4°C, and the precipitate was washed twice with pre-cooled PBS and resuspended in PBS for later use.

[0046] (2) Prepare liposomes using a thin film dispersion method. Dissolve a certain amount of lecithin in 3 mL of chloroform and perform rotary evaporation at 40°C for 1 h to form a uniform lipid film. Subsequently, hydrate the film with PBS to obtain a liposome suspension for later use.

[0047] (3) Preparation of ferrous sulfide nanomaterials. Dissolve 50 mg of bovine serum albumin powder in 6.0 mL of deionized water, and add 1 mL of ferrous chloride tetrahydrate solution (37 mM) and 1.5 mL of sodium sulfide solution (37 mM) in sequence under vigorous stirring (1200 rpm) to form a mixed solution. The mixture was reacted at 4°C for 12 h, and then dialyzed (MWCO: 8000-14000 Da) at 4°C for 12 h to obtain ferrous sulfide nanomaterials.

[0048] The ferrous sulfide nanomaterials were characterized by TEM, XPS and XRD. Figure 1 As shown in Figure 2, the synthesized ferrous sulfide nanomaterials are spherical with a diameter of 115±20 nanometers. XPS characterization Figure 2 As shown, Fe 2+ and Fe 3+Coexisting in ferrous sulfide nanomaterials. XRD characterization Figure 3 As shown, the XRD pattern of ferrous sulfide nanomaterials has no obvious diffraction peaks, indicating that the embedded ferrous sulfide nanomaterials are in an amorphous phase.

[0049] (4) Preparation of biomimetic membrane-wrapped ferrous sulfide nanomaterials. The neutrophil membrane, liposome suspension and ferrous sulfide nanomaterials prepared in steps (1), (2) and (3) were mixed in a mass ratio of 1:2:1.5. The mixture was placed in an ice bath and subjected to ultrasonic treatment by a probe (ultrasonic power 10%, working 3s, resting 2s, a total of 5min) to obtain biomimetic membrane-wrapped ferrous sulfide nanomaterials.

[0050] The biomimetic membrane and ferrous sulfide nanomaterials were labeled with fluorescent dyes DiO and RITC, respectively, and the cell nucleus was labeled with fluorescent dye DAPI. The co-localization of the biomimetic membrane and ferrous sulfide nanomaterials was observed by confocal microscopy. Figure 4 As shown in the figure, the DiO-labeled biomimetic membrane and the RITC-labeled ferrous sulfide nanomaterials can be co-localized, proving the successful integration of the biomimetic membrane and the ferrous sulfide nanomaterials. The ferrous sulfide nanomaterials wrapped in the biomimetic membrane were dissolved with sodium dodecyl sulfate, and the integrity of the membrane protein was characterized by Coomassie brilliant blue staining after PAGE gel electrophoresis, as shown in the figure. Figure 5 As shown, the groups represent: neutrophil membrane (NM), liposome (Lipo), neutrophil-based bionic carrier (NL), bionic membrane-wrapped ferrous sulfide nanomaterials (NL-FSB), bovine serum albumin (BSA), and bionic membrane-wrapped ferrous sulfide nanomaterials can retain the membrane protein components of the neutrophil membrane, and thus can inherit the bionic properties associated with neutrophils.

[0051] Example 2

[0052] (1) Neutrophils were extracted from the bone marrow of 6-week-old male ICR mice using a modified Percoll gradient method. The leg bones and femurs of the mice were first separated, and then the bone marrow was washed with RPMI 1640 medium, filtered through a 200 μm filter membrane, and centrifuged at 1700 rpm for 5 min. Subsequently, the red blood cells were lysed twice using red blood cell lysis buffer, and the cells were washed and resuspended with pre-cooled PBS. Next, 78%, 65%, and 55% percoll separation solutions were slowly added to the centrifuge tube in sequence, and finally the cell suspension was added, and centrifuged at 3120 rpm for 30 min. Neutrophils at the 65% and 78% Percoll interfaces were collected, washed three times with pre-cooled PBS, and resuspended. In order to activate neutrophils, 100 ng of LPS was added to stimulate the cells and cultured for 4 h at 37°C and 5% CO2. After the culture, the cell suspension was collected and centrifuged at 1700 rpm for 5 min, and then washed three times with pre-cooled PBS. Then, the cells were resuspended in deionized water and the neutrophil membranes were broken by repeated freezing-thawing. Specifically, the cell suspension was repeatedly frozen and cycled between -80°C and 37°C three times. Subsequently, the cell suspension was centrifuged at 15,000 rpm for 15 min, the neutrophil membranes were collected at 4°C, and the precipitate was washed twice with pre-cooled PBS and resuspended in PBS for later use.

[0053] (2) Prepare liposomes using a thin film dispersion method. Dissolve a certain amount of lecithin in 3 mL of chloroform and perform rotary evaporation at 40°C for 1 h to form a uniform lipid film. Subsequently, hydrate the film with PBS to obtain a liposome suspension for later use.

[0054] (3) Preparation of ferrous sulfide nanomaterials. 100 mg of bovine serum albumin powder was dissolved in 6.0 mL of deionized water, and 1 mL of ferrous chloride tetrahydrate solution (37 mM) and 1.5 mL of sodium sulfide solution (37 mM) were added in sequence under vigorous stirring (1200 rpm) to form a mixed solution. The mixture was reacted at 4°C for 12 h, and then dialyzed (MWCO: 8000-14000 Da) at 4°C for 12 h to obtain ferrous sulfide nanomaterials.

[0055] The TEM morphology of the ferrous sulfide nanomaterial prepared in this example shows that the synthesized ferrous sulfide nanomaterial is spherical with a diameter of 115±20 nanometers; XPS characterization shows that Fe 2+ and Fe 3+ Coexist in ferrous sulfide nanomaterials; XRD characterization shows that the XRD spectrum of ferrous sulfide nanomaterials has no obvious diffraction peaks, indicating that the embedded ferrous sulfide nanomaterials are an amorphous phase.

[0056] (4) Preparation of biomimetic membrane-wrapped ferrous sulfide nanomaterials. The neutrophil membrane, liposome suspension and ferrous sulfide nanomaterials prepared in steps (1), (2) and (3) were mixed in a mass ratio of 1:2:1.5. The mixture was placed in an ice bath and subjected to ultrasonic treatment by a probe (ultrasonic power 10%, working 3s, resting 2s, a total of 5min) to obtain biomimetic membrane-wrapped ferrous sulfide nanomaterials.

[0057] The biomimetic membrane and ferrous sulfide nanomaterial prepared in this embodiment were labeled with fluorescent dyes DiO and RITC, respectively, and the cell nucleus was labeled with fluorescent dye DAPI. The colocalization of the biomimetic membrane and the ferrous sulfide nanomaterial was observed by confocal microscopy. The biomimetic membrane labeled with DiO and the ferrous sulfide nanomaterial labeled with RITC were colocalized, proving the successful integration of the biomimetic membrane and the ferrous sulfide nanomaterial. The ferrous sulfide nanomaterial wrapped in the biomimetic membrane prepared in this embodiment was dissolved with sodium dodecyl sulfate, and the integrity of the membrane protein was characterized by Coomassie brilliant blue staining after PAGE gel electrophoresis. The ferrous sulfide nanomaterial wrapped in the biomimetic membrane can retain the membrane protein components of the neutrophil membrane, and thus can inherit the biomimetic properties related to the neutrophil.

[0058] Example 3

[0059] (1) Neutrophils were extracted from the bone marrow of 6-week-old male ICR mice using a modified Percoll gradient method. The leg bones and femurs of the mice were first separated, and then the bone marrow was washed with RPMI 1640 medium, filtered through a 200 μm filter membrane, and centrifuged at 1700 rpm for 5 min. Subsequently, the red blood cells were lysed twice using red blood cell lysis buffer, and the cells were washed and resuspended with pre-cooled PBS. Next, 78%, 65%, and 55% percoll separation solutions were slowly added to the centrifuge tube in sequence, and finally the cell suspension was added, and centrifuged at 3120 rpm for 30 min. Neutrophils at the 65% and 78% Percoll interfaces were collected, washed three times with pre-cooled PBS, and resuspended. In order to activate neutrophils, 100 ng of LPS was added to stimulate the cells and cultured for 4 h at 37°C and 5% CO2. After the culture, the cell suspension was collected and centrifuged at 1700 rpm for 5 min, and then washed three times with pre-cooled PBS. Then, the cells were resuspended in deionized water and the neutrophil membranes were broken by repeated freezing-thawing. Specifically, the cell suspension was repeatedly frozen and cycled between -80°C and 37°C three times. Subsequently, the cell suspension was centrifuged at 15,000 rpm for 15 min, the neutrophil membranes were collected at 4°C, and the precipitate was washed twice with pre-cooled PBS and resuspended in PBS for later use.

[0060] (2) Prepare liposomes using a thin film dispersion method. Dissolve a certain amount of lecithin in 3 mL of chloroform and perform rotary evaporation at 40°C for 1 h to form a uniform lipid film. Subsequently, hydrate the film with PBS to obtain a liposome suspension for later use.

[0061] (3) Preparation of ferrous sulfide nanomaterials. Dissolve 50 mg of bovine serum albumin powder in 6.0 mL of deionized water, and add 1 mL of ferrous chloride tetrahydrate solution (37 mM) and 1.5 mL of sodium sulfide solution (37 mM) in sequence under vigorous stirring to form a mixed solution. The mixture was reacted at 4°C for 6 h, and then dialyzed (MWCO: 8000-14000 Da) at 4°C for 12 h to obtain ferrous sulfide nanomaterials.

[0062] The TEM morphology of the ferrous sulfide nanomaterial prepared in this example shows that the synthesized ferrous sulfide nanomaterial is spherical; XPS characterization shows that Fe 2+ and Fe 3+ Coexist in ferrous sulfide nanomaterials; XRD characterization shows that the XRD spectrum of ferrous sulfide nanomaterials has no obvious diffraction peaks, indicating that the embedded ferrous sulfide nanomaterials are an amorphous phase.

[0063] (4) Preparation of biomimetic membrane-wrapped ferrous sulfide nanomaterials. The neutrophil membrane, liposome suspension and ferrous sulfide nanomaterials prepared in steps (1), (2) and (3) were mixed in a mass ratio of 1:2:1.5. The mixture was placed in an ice bath and subjected to ultrasonic treatment by a probe (ultrasonic power 10%, working 3s, resting 2s, a total of 5min) to obtain biomimetic membrane-wrapped ferrous sulfide nanomaterials.

[0064] The biomimetic membrane and ferrous sulfide nanomaterial prepared in this embodiment were labeled with fluorescent dyes DiO and RITC, respectively, and the cell nucleus was labeled with fluorescent dye DAPI. The colocalization of the biomimetic membrane and the ferrous sulfide nanomaterial was observed by confocal microscopy. The biomimetic membrane labeled with DiO and the ferrous sulfide nanomaterial labeled with RITC were colocalized, proving the successful integration of the biomimetic membrane and the ferrous sulfide nanomaterial. The ferrous sulfide nanomaterial wrapped in the biomimetic membrane prepared in this embodiment was dissolved with sodium dodecyl sulfate, and the integrity of the membrane protein was characterized by Coomassie brilliant blue staining after PAGE gel electrophoresis. The ferrous sulfide nanomaterial wrapped in the biomimetic membrane can retain the membrane protein components of the neutrophil membrane, and thus can inherit the biomimetic properties related to the neutrophil.

[0065] Example 4

[0066] (1) Neutrophils were extracted from the bone marrow of 6-week-old male ICR mice using a modified Percoll gradient method. The leg bones and femurs of the mice were first separated, and then the bone marrow was washed with RPMI 1640 medium, filtered through a 200 μm filter membrane, and centrifuged at 1700 rpm for 5 min. Subsequently, the red blood cells were lysed twice using red blood cell lysis buffer, and the cells were washed and resuspended with pre-cooled PBS. Next, 78%, 65%, and 55% percoll separation solutions were slowly added to the centrifuge tube in sequence, and finally the cell suspension was added, and centrifuged at 3120 rpm for 30 min. Neutrophils at the 65% and 78% Percoll interfaces were collected, washed three times with pre-cooled PBS, and resuspended. In order to activate neutrophils, 100 ng of LPS was added to stimulate the cells and cultured for 4 h at 37°C and 5% CO2. After the culture, the cell suspension was collected and centrifuged at 1700 rpm for 5 min, and then washed three times with pre-cooled PBS. Then, the cells were resuspended in deionized water and the neutrophil membranes were broken by repeated freezing-thawing. Specifically, the cell suspension was repeatedly frozen and cycled between -80°C and 37°C three times. Subsequently, the cell suspension was centrifuged at 15,000 rpm for 15 min, the neutrophil membranes were collected at 4°C, and the precipitate was washed twice with pre-cooled PBS and resuspended in PBS for later use.

[0067] (2) Prepare liposomes using a thin film dispersion method. Dissolve a certain amount of lecithin in 3 mL of chloroform and perform rotary evaporation at 40°C for 1 h to form a uniform lipid film. Subsequently, hydrate the film with PBS to obtain a liposome suspension for later use.

[0068] (3) Preparation of ferrous sulfide nanomaterials. Dissolve 50 mg of bovine serum albumin powder in 6.0 mL of deionized water, and add 1 mL of ferrous chloride tetrahydrate solution (37 mM) and 1.5 mL of sodium sulfide solution (37 mM) in sequence under vigorous stirring to form a mixed solution. The mixture was reacted at 4°C for 12 h, and then dialyzed (MWCO: 8000-14000 Da) at 4°C for 12 h to obtain ferrous sulfide nanomaterials.

[0069] The ferrous sulfide nanomaterials were characterized by TEM, XPS and XRD. The TEM morphology of the ferrous sulfide nanomaterials prepared in this example shows that the synthesized ferrous sulfide nanomaterials are spherical with a diameter of 115±20 nanometers; XPS characterization shows that Fe 2+ and Fe 3+ Coexist in ferrous sulfide nanomaterials; XRD characterization shows that the XRD spectrum of ferrous sulfide nanomaterials has no obvious diffraction peaks, indicating that the embedded ferrous sulfide nanomaterials are an amorphous phase.

[0070] (4) Preparation of biomimetic membrane-wrapped ferrous sulfide nanomaterials. The neutrophil membrane, liposome suspension and ferrous sulfide nanomaterials prepared in steps (1), (2) and (3) were mixed in a mass ratio of 1:2:3. The mixture was placed in an ice bath and subjected to ultrasonic treatment by a probe (ultrasonic power 10%, working 3s, resting 2s, a total of 5min) to obtain biomimetic membrane-wrapped ferrous sulfide nanomaterials.

[0071] The biomimetic membrane and ferrous sulfide nanomaterial prepared in this embodiment were labeled with fluorescent dyes DiO and RITC, respectively, and the cell nucleus was labeled with fluorescent dye DAPI. The colocalization of the biomimetic membrane and the ferrous sulfide nanomaterial was observed by confocal microscopy. The biomimetic membrane labeled with DiO and the ferrous sulfide nanomaterial labeled with RITC were colocalized, proving the successful integration of the biomimetic membrane and the ferrous sulfide nanomaterial. The ferrous sulfide nanomaterial wrapped in the biomimetic membrane prepared in this embodiment was dissolved with sodium dodecyl sulfate, and the integrity of the membrane protein was characterized by Coomassie brilliant blue staining after PAGE gel electrophoresis. The ferrous sulfide nanomaterial wrapped in the biomimetic membrane can retain the membrane protein components of the neutrophil membrane, and thus can inherit the biomimetic properties related to the neutrophil.

[0072] Performance test

[0073] (1) Evaluation of ROS production performance and in vitro evaluation of reactive oxygen species

[0074] (1.1) The biomimetic membrane-wrapped ferrous sulfide nanomaterial (prepared in Example 1, 20 μg) and 20 μl of TMB solution (50 mM) were dispersed in acetic acid / sodium acetate buffer (2 mL, pH=5.0).

[0075] The oxidation of TMB by ROS produced by ferrous sulfide nanomaterials wrapped in biomimetic membranes at different time periods (1, 3, 5, 7, 10, 15 and 20 min) was detected by UV-visible spectroscopy. Figure 6 As shown, the absorbance of TMB did not change significantly over time, indicating that the ferrous sulfide nanomaterials wrapped in the biomimetic membrane could not induce the production of ROS in the absence of the catalytic substrate H2O2.

[0076] (1.2) The biomimetic membrane-wrapped ferrous sulfide nanomaterial (prepared in Example 1, 20 μg), 20 μl of H2O2 solution (1 M), and 20 μl of TMB solution (50 mM) were dispersed in acetic acid / sodium acetate buffer (2 mL, pH = 5.0).

[0077] The oxidation of TMB by ROS produced by ferrous sulfide nanomaterials wrapped in biomimetic membranes at different time periods (1, 3, 5, 7, 10, 15 and 20 min) was detected by UV-visible spectroscopy. Figure 7As shown, the absorbance of TMB increased dramatically with time, indicating that the biomimetic membrane-wrapped ferrous sulfide nanomaterials can significantly induce the production of ROS in the presence of the catalytic substrate H2O2.

[0078] (2.3) By comparison Figure 6 and Figure 7 The presence of H2O2 can significantly promote the efficiency of ROS production induced by ferrous sulfide nanomaterials wrapped in bionic membranes.

[0079] (2) H2S release performance evaluation

[0080] The biomimetic membrane-wrapped ferrous sulfide nanomaterial obtained in Example 1 was dispersed in phosphate buffers of different pH values ​​(pH=7.4, 6.5 and 5.5) to obtain a certain concentration of biomimetic membrane-wrapped ferrous sulfide nanomaterial phosphate buffer solution (500 μg / ml), and incubated at 37°C, 200 rpm. Subsequently, the biomimetic membrane-wrapped ferrous sulfide nanomaterial solution was collected at different time periods, the supernatant was collected by centrifugation, and the H2S content in the supernatant was detected using an H2S detection kit. The results are shown in FIG. Figure 8 As shown, the bionic membrane-wrapped ferrous sulfide nanomaterials exhibited acid-responsive H2S release, laying the foundation for the specific release of H2S in the acidic microenvironment of tumors, thereby inhibiting the CAT activity of tumor cells.

[0081] (3)Fe 2+ Release detection

[0082] The biomimetic membrane-wrapped ferrous sulfide nanomaterial obtained in Example 1 was dispersed in phosphate buffers of different pH values ​​(pH=7.4, 6.5 and 5.5) to obtain a phosphate buffer solution (500 μg / ml) of the biomimetic membrane-wrapped ferrous sulfide nanomaterial at a certain concentration, and 1,10-phenanthroline was used as Fe 2+ The indicator was incubated at 37°C and 200 rpm. Then, the ferrous sulfide nanomaterial solution was collected at different time periods, the supernatant was collected by centrifugation, and its absorbance value at 510 nm was detected by UV-visible spectroscopy. The results are shown in Fig. 9 As shown, the biomimetic membrane-wrapped ferrous sulfide nanomaterials exhibit acidity-dependent Fe 2+ Release, laying the foundation for the bionic membrane-wrapped ferrous sulfide nanomaterials to catalyze the production of ROS in the acidic microenvironment of tumors.

[0083] (4) Cytotoxicity evaluation on breast cancer cell lines

[0084] Breast cancer cell line (4T1 cells) in logarithmic growth phase was taken and 1×10 4The cell density of cells was 100 μL / well. The cells were inoculated in a 96-well plate (200 μL / well) with RPMI 1640 culture medium containing 10% fetal bovine serum and cultured in an incubator at 37°C and 5% CO2. After the cells were cultured for 12 hours, the culture medium was replaced with a culture medium containing a biomimetic membrane-wrapped ferrous sulfide nanomaterial (prepared according to the method of Example 1), wherein the drug concentration (Fe content) was 0, 1.25, 2.5, 5, 10, 20, 40 and 80 μg / mL, respectively. After continuing to culture for 24 hours, the old culture medium was aspirated and washed once with PBS buffer. Subsequently, MTT solution (100 μL / well) was added to the wells, incubated in an incubator at 37°C and 5% CO2 for 1 to 4 hours, then the MTT solution was aspirated, 100 μL DMSO solution was added, and the system was shaken and shaken, and its optical density OD value was measured on an ELISA instrument.

[0085] Data processing: Use the corresponding software of the microplate reader to process the data, calculate the average OD value of 5 wells of each sample, and use the average value to calculate the cell viability (Cell Viability %) according to the following formula.

[0086] Cell Viability % = average OD value of sample group / average OD value of blank control group × 100% (Cell Viability % = OD sample / OD control ×100%)

[0087] Results Fig.10 .Depend on Fig.10 The analysis shows that the biomimetic membrane-wrapped ferrous sulfide nanomaterials exhibit obvious concentration-dependent cytotoxicity. Therefore, the biomimetic membrane-wrapped ferrous sulfide nanomaterials can produce obvious cytotoxicity after being taken up by tumor cells.

[0088] (5) Evaluation of tumor inhibition effect

[0089] Fifteen BALB / c female mice were breast-pad-bearing to construct an orthotopic breast cancer model. The mice were randomly divided into three groups, each with five mice, namely, a PBS group, a ferrous sulfide nanomaterial group (FSB) (prepared according to the method of this Example 1), and a biomimetic membrane-wrapped ferrous sulfide nanomaterial group (NL-FSB) (prepared according to the method of this Example 1). The drugs were administered via the tail vein every other day, and the tumor volume (V) of the primary tumor was measured at the same time. The calculation formula was: V = L × W 2 / 2, W and L are the widest and longest diameters of the tumor, respectively. The tumor volume was calculated to monitor the tumor inhibition effect.

[0090] The results are as follows Fig.11 The bionic membrane-wrapped ferrous sulfide nanomaterial group can significantly inhibit the growth of primary tumors and has a good tumor-suppressing effect.

[0091] The above-described embodiments provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above descriptions are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements and equivalent substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing ferrous sulfide nanomaterials wrapped by a bionic membrane based on neutral particles, characterized in that: The preparation method comprises the following steps: S1. dissolving bovine serum albumin in deionized water, adding ferrous chloride tetrahydrate solution and sodium sulfide solution to obtain a mixed solution, and reacting to obtain albumin-embedded amorphous ferrous sulfide nanomaterials; S2. Mixing the neutrophil membrane solution, the liposome solution and the albumin-embedded amorphous ferrous sulfide nanomaterial, and subjecting the mixture to ultrasonic treatment to obtain the bionic membrane-wrapped ferrous sulfide nanomaterial.

2. The method for preparing the ferrous sulfide nanomaterial wrapped by the biomimetic membrane according to claim 1, characterized in that: In step S1, the feeding ratio of bovine serum albumin, deionized water, ferrous chloride tetrahydrate and sodium sulfide is 10-100 mg: 4-12 mL: 2-12 mg: 1-8 mg.

3. The method for preparing the ferrous sulfide nanomaterial wrapped by the biomimetic membrane according to claim 1, characterized in that: In step S1, ferrous chloride tetrahydrate solution and sodium sulfide solution are added in sequence under stirring at 1200 rpm or higher, and the reaction is carried out at 1-8° C. for 6-24 hours.

4. The method for preparing the ferrous sulfide nanomaterial wrapped by the biomimetic membrane according to claim 1, characterized in that: In step S1, the particle size of the albumin-embedded amorphous ferrous sulfide nanomaterial is 50 to 150 nanometers.

5. The method for preparing the biomimetic membrane-wrapped ferrous sulfide nanomaterial according to claim 1, characterized in that: In step S2, the neutrophil membrane is extracted by the Percoll gradient method and obtained by repeated freeze-thaw and centrifugation; the liposome is prepared by a thin film dispersion method, the lipid used is lecithin, the solvent is chloroform, the rotary evaporation time is 0.5 to 4 hours, and the temperature is 20 to 60°C.

6. The method for preparing the biomimetic membrane-wrapped ferrous sulfide nanomaterial according to claim 1, characterized in that: In step S2, the feed ratio of the neutrophil membrane, liposome and ferrous sulfide nanomaterial is 0.5-2 mg: 1-4 mg: 0.5-6 mg.

7. The method for preparing the biomimetic membrane-wrapped ferrous sulfide nanomaterial according to claim 1, characterized in that: In step S2, the power of the ultrasonic treatment is 8-20%, and the treatment time is 2-10 minutes.

8. A ferrous sulfide nanomaterial wrapped by a biomimetic membrane obtained by the preparation method according to any one of claims 1 to 7.

9. Use of the ferrous sulfide nanomaterial wrapped by the bionic membrane according to claim 8 in preparing drugs for treating tumors.

10. The use of the ferrous sulfide nanomaterial wrapped by the bionic membrane according to claim 9, characterized in that: The bionic membrane-wrapped ferrous sulfide nanomaterial is used in the preparation of specific tumor-targeting and tumor-inhibiting drugs.